Skin in the game: Microequity and mentorship for online freelancing-based microentrepreneurs in Bangladesh - Bakhtiar, M. Mehrab; Meki, Muhammad; Quinn, Simon; Shonchoy, Abu (Private Enterprise Development in Low-Income Countries (PEDL), 2021)
In this pilot project, we demonstrate the exciting potential of online freelancing for improving the incomes of poor youth in rural Bangladesh. We also highlight the constraints to this type of work: financing constraints for the high training cost, access to the necessary work infrastructure, and soft skills requirements to success in the market. We shed light on some promising possibilities for innovative financing contracts and for ‘virtual exporting companies’ to act as freelancing incubators and assist students in their development.